Automation and critical evaluation of an annular chamber for aquatic ectotherm temperature preference experiments. Issue 6 (2nd April 2013) - Reiser, Stefan; Temming, Axel; Eckhardt, André; Herrmann, Jens‐Peter; Freckleton, Robert
Summary Annular chambers represent a novel approach for thermal preference experiments in aquatic ectothermic organisms. Most approaches using annular chambers so far lack automation in data recording and analysis, making temperature preference experiments laborious and time consuming. Here, we describe the design and construction of a modified version of an annular chamber system. We conducted extensive tests to improve the systems' functionality and confirm accuracy of the thermal gradient. Additionally, we present an automated matlab routine for data recording and analysis of temperature preference experiments using the common brown shrimp (Crangon crangon, L.) as a test organism. Using this automated routine, we performed an in silico comparison of different thermal gradient representations with various complexities to test for the effect of temperature resolution on the accuracy of thermal preference estimates. The here presented annular chamber produced a stable thermal gradient of ∆23 °C, ranging between 3 and 25 °C. Automated recording and data analysis facilitated implementation of long‐term experiments and allowed the collection of highly resolved preference data. The in silico comparison revealed a more accurate specification of the preference zone with increasing resolution of the temperature gradient. With regard to spatial resolution of the thermal gradient and assignment of position and temperature data, the in silico comparison demonstrated previous approaches to be inappropriate for benthic and passive species. We present guidelines for annular chamber construction and automation of data analysis in these systems, making annular chambers more handy and applicable for a wide range of preference studies. Besides its use for experiments in annular chambers, the principle of the here presented automated matlab routine can be applied to a wide range of behavioural and preference studies.